The megisthanid mites (Mesostigmata: Megisthanidae) of Australia - Seeman, Owen D. (Zootaxa, 2019)
The Australian Megisthanidae are revised, resulting in the description of five new species from passalid beetles (Coleoptera: Passalidae) in Queensland: M. manonae sp. nov. from Mastachilus australasicus; M. simoneae sp. nov. from Mastachilus polyphyllus; M. southcotti sp. nov. from Aulacocyclus fracticornis; M. womersleyi sp. nov. from Protomocoelus australis; and M. zachariei sp. nov. from Aulacocyclus kaupii. Megisthanus womersleyi is also based on material from Misima Island, Papua New Guinea, originally identified as Megisthanus doreianus Thorell, 1882. Megisthanus modestus Berlese, 1910, is redescribed based on material from Pharochilus spp. collected from Canberra, New South Wales, Queensland and Tasmania. The Papua New Guinean species Mastachilus papuanus Womersley, 1937 is diagnosed and discussed in relation to the other species from New Guinea. Additional collections of Megisthanus leviathanicus Seeman, 2017 and M. thorelli Womersley, 1937 are also reported. A genus description and a key to the eight Australian species of Megisthanus are provided.